Berlin w roku 1933. Wokół reportaży Zygmunta Nowakowskiego - Wroniszewski, Maksymilian (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
The article focuses on the news coverage of Zygmunt Nowakowski. They illustrate the nature of change in Germany after Adolf Hitler’s coming to power. The attention is focused mainly on the changes of social relations and the modification of the space of German cities, e.g. manifested in its symbolization and militarization